Management Skills - Singleton, W.T. author. aut Link
XVI, 303 p.
Keywords: w. T. SINGLETON THE CONCEPT This is the third in a series of books devoted to the study of real skills. The topic is management. A book on social skills is still to come and it might seem that the sequence should be reversed on the grounds that social skills are obviously one element in management skills but it is appropriate to deal with management first on the criterion of increasing complexity. Management skills are easier to understand than general social skills. This is because the defining characteristic of a skill is a purpose. The purpose of organizations in which managers operate and the tasks in which they are engaged are not easy to define but they are certainly less obscure than are the more general purposes of communities and people interactions in which the complete range of social skills is practised. Skills, like purposes, are inherently to do with people. It follows that the 'skills view' of management will be as a people-based activity. Individuals carry out management tasks and these tasks always involve other individuals, of whom some are subordinate, some superior and some equivalent within the hierarchy of the particular management organization. The concept of a hierarchy is as central to management as it is to skills. The alternative to hier archy is anarchy. Management is not solely concerned with people.